(untitled) (BIS Humanities and Social Science, 2026)
First-year Communication Science students often experience communication apprehension during the transition from high school to university, particularly as they adapt to new academic demands, lecturer communication styles, peer interactions, and diverse campus cultures. This condition is more prominent among the 2024 cohort of Communication Science students at Universitas Muhammadiyah Yogyakarta, who grew up in the post-pandemic digital era and are more accustomed to online communication than face-to-face interaction. This study aims to identify the strategies used by new students to reduce communication apprehension. Using a qualitative case study approach, data were collected through observation, interviews, and documentation involving ten informants, consisting of five male and five female students. Data were analyzed using the Miles and Huberman interactive model. The findings show that students experience two forms of uncertainty: cognitive uncertainty, related to limited understanding of lecturers’ and peers’ thoughts and communication styles, and behavioral uncertainty, reflected in confusion about how to act or respond in campus social situations. To reduce uncertainty, students apply three strategies from Berger and Calabrese’s Uncertainty Reduction Theory: passive strategies through observation, active strategies through information seeking from third parties, and interactive strategies through direct communication. Passive strategies were found to be the most used during the early stage of university adaptation.